ONE VILLAGE ONE BRAND, AN ALTERNATIVE CONCEPT PERSPECTIVE TO IMPROVE MEDIUM SMALL BUSINESSES - SUGENG EKO YULI WALUYO waluyo (International Interdisciplinary Conference on Sustainable Development Goals, 2020)
ABSTRACT Products from the village are always unable to compete with products from areas close to the city. In fact, in terms of quality, products from the village are of the same quality as products from areas near the city, even better. Several problems regarding the rural economy include: low economies of scale, weak market access, long distribution channels, low post-harvest facilities, and finally the difficulty of capital. In Presidential Regulation number 59 of 2017 concerning the implementation of achieving the national Sustainable Development Goals (SDGs). Then implemented through Presidential Decree number 13 of 2020 concerning priority use of village funds in 2021. The purpose of this study is to describe the government's efforts to implement the village's Sustainable Development Goals (SDGs) agenda in order to increase economic growth in rural areas through One Village One Brand. This research is very urgent because with the One Village One Brand program, it can help accelerate government programs through the Ministry of Health as stated in the SDGs at the point of equitable village economic growth. The method in this study uses a Systematic Literature Review (SLR) by examining several sources used as material in searching and obtaining literature. These sources are used as the basis for analyzing and deriving a conclusion in making the results of the study. This research can show that the government's efforts to improve the rural economy through One village one brand which is supported by village funds make the rural economy grow rapidly. So that the welfare of the village community can increase. With the One village One Brand, it will improve the image of the village and the characteristics of the village. Keywords: One Village One Brand, an alternative concept, small and medium enterprises